Early protection against measles infection in children Immunized with DPT-measles Vaccine at the Age of 4 Months - Soegeng Soegijanto; Dwi Atmaji Soejono; Parwati Setiono B. (Indonesian Pediatric Society Publishing House, 2018)
A study on early immunization with DPT-measles vaccine at the age of 4 months, was earned out during 1990 - 1991 on 348 babies at the Health Centre of Surabaya regency. Three hundred and forty eight babies were served as control. The results of the study reported here were : (a) By giving a mixture of DPT and measles at an early age (4 months of age) the coverage of measles immunization could be increased to 21% - 27%. (b) 1'wenty two percents of measles cases could be prevented. (c) The geometric mean titer using hemagglutination inhibition test of the babies who got a mixture DP7~measles vaccination at an early age was significantly higher than that of the GMT HI test of babies who got measles vaccination at the age of 9 months ( z test, p <0, 05 ) . The result of analysis of data showed that an early immunization program using a mixture of DPT-measles could protect babies under 9 months and thus prevent them from measles infection.